(untitled) (Medical Forum Monthly, 2025)
Objective: To assess the association between central obesity (waist-to height ratio >0.5) and liver fibrosis, steatosis, and inflammatory biomarkers in metabolic dysfunction-associated steatotic liver disease patients. Study Design: A case-control study Place and Duration of Study: This study was conducted at the Department of Medicine, College of Medicine, AL- Iraqia of University, Iraq from 15th March 2024 to 30th May 2025. Methods: A case-control study was conducted on 120 adults diagnosed with metabolic dysfunction-associated steatotic liver disease in Baghdad. Participants were divided into centrally obese (n=60) and non-obese (n=60)groups. Clinical and biochemical parameters including liver enzymes (alanine aminotransferase, aspartate aminotransferase), C-reactive protein, homeostatic model assessment for insulin resistance and Fibro scan-based fibrosis staging were compared. Results: Centrally obese patients showed significantly elevated alanine aminotransferase (49.7 vs. 33.1 U/L, p<0.001), C-reactive protein (19.9 vs. 9.7 mg/L, p<0.001), and homeostatic model assessment for insulin resistance (5.93 vs. 3.39, p<0.001). Fibrosis grades ≥F2 and steatosis stages ≥ S2 were significantly more frequent among the obese group (p<0.01). Conclusion: Central obesity is significantly associated with worsened liver fibrosis and metabolic derangement in metabolic dysfunction-associated steatotic liver disease patients. These findings support the utility of waist to hip ratio as a clinical screening tool in metabolic dysfunction-associated steatotic liver disease management.